Manajemen Kinerja Sekretariat Daerah Kabupaten Halmahera Barat Terkait Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) - Mangar, Jembris; Mingkid, Elfie; Kawung, Evelin (Sam Ratulangi University, 2021)
Performance management is adapted into a government agency performanceaccountability system which includes a systematic and continuous process. The implementationof a performance accountability system for government agencies which includes performanceplanning, performance measurement, performance reporting, and performance evaluation,which aims to increase accountability for government performance. This research wasconducted by analyzing the performance management of the West Halmahera DistrictSecretariat related to the Government Agency Performance Accountability System (SAKIP)which is associated with the performance management cycle theory approach (The PerformanceManagement Cycle). In this study using a qualitative research type. The data collectionprocedure in this research is by interviewing 7 (seven) selected informants and documentsrelated to the issues raised. Data analysis was carried out by means of data reduction, datapresentation and drawing conclusions or data verification. The results of the research obtainedare that the Regional Secretariat of West Halmahera Regency has implemented the concept ofperformance management, but so far each stage is still not optimal, such as the low quality ofperformance planning documents, performance measurement is not on target, slow performancereporting and internal performance evaluation is not optimal so that the performanceaccountability of the Regional Secretariat of West Halmahera Regency has not been satisfactory.Efforts or strategies to increase the performance accountability of the Regional Secretariat ofWest Halmahera Regency, namely by improving the quality of performance planning documents,implementing technical training / guidance to improve the quality of human resources, and moreoften carrying out internal evaluations with the aim of following up quickly on anyrecommendations from the results of work program evaluations.Keywords: Performance Management. SAKIP